The Effectiveness of Green Belt Vegetation in Reducing Air Pollution and Noise - Firnawati, Firnawati; Rizqiyah , Umara Hasmarani; Muhibuddin , Andi Firman (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Rapid urbanization and industrialization in the modern world have led to increased urban pollution. Road traffic is considered a major source of air and noise pollution, negatively impacting the environment and human health. Roadside green infrastructure, also known as green belts, has the potential to reduce air pollution and noise from traffic by increasing the distribution of plants that effectively absorb pollutants. Vegetation along roads, in addition to acting as a noise barrier, also plays a role in controlling urban air pollution. Studies show that plants can reduce air pollutant content through natural absorption and filtration processes. Meanwhile, noise reduction by vegetation is influenced by the type of vegetation, the level of vegetation density, and the planting combination. The type of vegetation is related to the thickness and flexibility of the leaves. The plant with the highest dust absorption capacity is the Mango Tree (Mangifera indica) at 0.531 g/m2 . Then the second highest is the Saga Tree (Adenanthera pavonina ) at 0.224 g/ m2 . Meanwhile, the Kaya Tree (Khaya anthotheca) has the lowest dust absorption capacity, namely 0.212 g/m 2 . Land with vegetation is more effective in reducing noise compared to land without vegetation. The greater the distance from the noise source, the higher the level of noise reduction, with a distance of 10 m being set as the minimum limit for green belts.